2012
DOI: 10.1371/journal.pone.0046782
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses to Smoking Stimuli Are Influenced by Smokers' Attitudes towards Their Own Smoking Behaviour

Abstract: An important feature of addiction is the high drug craving that may promote the continuation of consumption. Environmental stimuli classically conditioned to drug-intake have a strong motivational power for addicts and can elicit craving. However, addicts differ in the attitudes towards their own consumption behavior: some are content with drug taking (consonant users) whereas others are discontent (dissonant users). Such differences may be important for clinical practice because the experience of dissonance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A meta-analysis of fMRI studies on smoking cue reactivity also concluded that smoking cues, as compared to neutral cues, reliably evoke larger fMRI responses in the insula (Engelmann et al, 2012). The effect of smoking initiation-related cues (e.g., lighter) vs. smoking conclusion-related cues (e.g., cigarette butt in ashtray) on two groups of smokers who were either content or discontent with their behavior further examined temporal relations of smoking cues (Stippekohl et al, 2012), with discontent smokers showed greater insular activation in response to initiation-related cues than content smokers, and aIC activation is observed during intrinsic, but not extrinsic, motivation (Lee and Reeve, 2013).…”
Section: Clinical Evidence For the Insulamentioning
confidence: 99%
“…A meta-analysis of fMRI studies on smoking cue reactivity also concluded that smoking cues, as compared to neutral cues, reliably evoke larger fMRI responses in the insula (Engelmann et al, 2012). The effect of smoking initiation-related cues (e.g., lighter) vs. smoking conclusion-related cues (e.g., cigarette butt in ashtray) on two groups of smokers who were either content or discontent with their behavior further examined temporal relations of smoking cues (Stippekohl et al, 2012), with discontent smokers showed greater insular activation in response to initiation-related cues than content smokers, and aIC activation is observed during intrinsic, but not extrinsic, motivation (Lee and Reeve, 2013).…”
Section: Clinical Evidence For the Insulamentioning
confidence: 99%
“…Some authors have shown that one’s intention to quit can impact prefrontal and limbic activity toward cigarette pictures ( 48 ) Furthermore, it was shown that smokers who are dissatisfied with their smoking behavior, relative to those more accepting of their tobacco use, were more reactive (e.g., orbitofrontal and limbic activations) to appetitive cigarette cues ( 49 ).…”
Section: Sources Of Heterogeneitymentioning
confidence: 99%
“…Some of the inconsistencies in the field are likely due to clinical or demographic factors that act as moderators, such as the differences between classes of drug (e.g., stimulants vs. opiates) (McNamara et al, 2010), gender (Potenza et al, 2012), or treatment-seeking status (Stippekohl et al, 2012). Inclusion criteria are obviously important; for example, the target group in the Peters et al's (2011) study were adolescents who reported smoking at least one cigarette in the last 30 days, while Jia et al (2011) included cocaine users seeking treatment for dependence.…”
Section: Neural Processing Of Reward In Drug Addictionmentioning
confidence: 99%